Effectiveness of Concept Mapping: A Constructivist based Educational Strategy on Grade Seven Arab Students' Academic Achievement in Chemistry - Thomas, Nimmy M. (2016)
The present study aimed to determine the effects of concept mapping, a constructivist based learning strategy, on academic achievement in chemistry. The participants were 64 grade seven students in a K-12 British curriculum private school in Dubai, the United Arab Emirates. The study employed a quasi-experimental, pre-test, post-test design using an achievement test called CMAT (Chemistry Matter Achievement Test). The experimental group were taught a topic in chemistry with concept mapping strategy for a period of four weeks and the control group were taught the same topic using expository method for the same period of time. The data collected were analyzed using descriptive and inferential statistics. The mean post test score of the experimental group was found to significantly be higher than the mean post test score of the control group. Results showed that concept mapping is an effective strategy for teaching and learning chemistry concepts. The data analysis also revealed that the concept mapping strategy is capable of enhancing learners’ mastery of content at higher order levels of cognition. The findings of this study recommended that chemistry educators should use concept mapping strategy as a pedagogical and evaluation tool as it can enhance students’ meaningful understanding of chemistry concepts, longer retention of information and academic performance in the subject content.